ISLAMIC RELIGIOUS EDUCATION LEARNING STRATEGIES BASED ON AI TECHNOLOGY TO IMPROVE ISLAMIC UNDERSTANDING AND CHARACTER IN THE SOCIETY 5.0 ERA - Raihanah; Siti Fajrianti; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The rapid development of artificial intelligence (AI) technology has opened up new opportunities in education in the 5.0 era, including in Islamic Religious Education teaching. However, the application of this technology still faces challenges in upholding the moral and spiritual values at the core of religious education. This study aims to analyze the implementation of AI based learning strategies in Islamic Religious Education subjects and their impact on students' understanding of Islamic material and forming Islamic characters. The method used in this research is a literature review with a qualitative descriptive approach, which examines various relevant literature sources from previous research. The results show that using AI, such as Islamic chatbots, adaptive self learning, and AR/VR technology, can improve the quality of learning, the effectiveness of students' understanding of religious material, and the internalization of moral values. However, the use of AI must be controlled to avoid diminishing the role of teachers as moral role models and to maintain the emphasis on Islamic principles in the learning process. AI can effectively strengthen Islamic education in the digital age with the right strategy.